Repurposing Clinical Molecule Ebselen to Combat Drug Resistant Pathogens. - Shankar Thangamani; Waleed Younis; Mohamed N Seleem (PLoS ONE, 2015)
Without a doubt, our current antimicrobials are losing the battle in the fight against newly-emerged multidrug-resistant pathogens. There is a pressing, unmet need for novel antimicrobials and novel approaches to develop them; however, it is becoming increasingly difficult and costly to develop new antimicrobials. One strategy to reduce the time and cost associated with antimicrobial innovation is drug repurposing, which is to find new applications outside the scope of the original medical indication of the drug. Ebselen, an organoselenium clinical molecule, possesses potent antimicrobial activity against clinical multidrug-resistant Gram-positive pathogens, including Staphylococcus, Streptococcus, and Enterococcus, but not against Gram-negative pathogens. Moreover, the activity of ebselen against Gram-positive pathogens exceeded those activities determined for vancomycin and linezolid, drugs of choice for treatment of Enterococcus and Staphylococcus infections. The minimum inhibitory concentrations of ebselen at which 90% of clinical isolates of Enterococcus and Staphylococcus were inhibited (MIC90) were found to be 0.5 and 0.25 mg/L, respectively. Ebselen showed significant clearance of intracellular methicillin-resistant S. aureus (MRSA) in comparison to vancomycin and linezolid. We demonstrated that ebselen inhibits the bacterial translation process without affecting mitochondrial biogenesis. Additionally, ebselen was found to exhibit excellent activity in vivo in a Caenorhabditis elegans MRSA-infected whole animal model. Finally, ebselen showed synergistic activities with conventional antimicrobials against MRSA. Taken together, our results demonstrate that ebselen, with its potent antimicrobial activity and safety profiles, can be potentially used to treat multidrug resistant Gram-positive bacterial infections alone or in combination with other antibiotics and should be further clinically evaluated.